Effect of Micro-Teaching Accompanied by Interactive Video on Students’ Learning of Some Basic Futsal Skills - Da'is, Rafid Waleed (STKIP Taman Siswa Bima, 2025)
This study investigates the effect of micro-teaching accompanied by interactive video on students’ acquisition of basic futsal skills. The background of this research lies in the need to improve teaching effectiveness in physical education, particularly in skill-based sports like futsal. Traditional teaching approaches often lack individual feedback and technological support, which are crucial for enhancing skill learning. Objective. the study aims to design an educational program based on the micro-teaching method supported by interactive video to enhance students' mastery of selected futsal skills. The research employed an experimental design suitable for assessing the impact of an instructional intervention. The participants consisted of 30 third-year students from the College of Physical Education and Sports Sciences at the University of Basra. The intervention included structured micro-teaching sessions integrated with interactive video content targeting three core futsal skills: passing, scoring, and dribbling. Standardized tests were conducted before and after the intervention to measure student performance. The results demonstrated significant improvement in all three skills among the participants following the program. These findings indicate that the integration of micro-teaching and interactive video is an effective instructional approach for teaching technical skills in futsal. Conclusion, the study confirms the value of micro-teaching paired with interactive video in promoting skill acquisition in physical education. As a contribution to the field, it recommends incorporating this blended teaching method in sports training and education curricula to optimize student engagement, feedback, and performance outcomes.